Livelihood and Landscape Change in Africa: Future Trajectories for Improved Well-Being under a Changing Climate - Speranza, Chinwe Ifejika (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book is based on a Special Issue of the journal LAND that draws together a collection of 11 diverse articles at the nexus of climate change, landscapes, and livelihoods in rural Africa; all explore the links between livelihood and landscape change, including shifts in farming practices and natural resource use and management. The articles, which are all place-based case studies across nine African countries, cover three not necessarily mutually exclusive thematic areas, namely: smallholder farming livelihoods under new climate risk (five articles); long-term dynamics of livelihoods and landscape change and future trajectories (two articles); and natural resource management and governance under a changing climate, spanning forests, woodlands, and rangelands (four articles). The commonalities, key messages, and research gaps across the 11 articles are presented in a synthesis article. All the case studies pointed to the need for an integrated and in-depth understanding of the multiple drivers of landscape and livelihood change and how these interact with local histories, knowledge systems, cultures, complexities, and lived realities. Moreover, where there are interventions (such as new governance systems, REDD+ or climate smart agriculture), it is critical to interrogate what is required to ensure a fair and equitable distribution of emerging benefits.